2015
DOI: 10.1021/acs.jpcb.5b03674
|View full text |Cite
|
Sign up to set email alerts
|

What Determines CO2 Solubility in Ionic Liquids? A Molecular Simulation Study

Abstract: Molecular dynamics (MD) simulations of 10 different pure and CO2-saturated ionic liquids are performed to identify the factors that determine CO2 solubility. Imidazolium-based cations with varying alkyl chain length and functionalization are paired with anions of different hydrophobicity and size. Simulations are carried out with an empirical force field based on liquid-phase charges. The partial molar volume of CO2 in ionic liquids (ILs) varies from 30 to 40 cm(3)/mol. This indicates that slight ion displacem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 63 publications
6
68
0
Order By: Relevance
“…2 for a listing) and data for simple high-temperature molten salts. 1, 84 One may speculate that this change in ∆ is due to the "existence of a polar network formed by the charged moieties of the molecular ions" and "separations between different strands of the polar network caused by a continuous nonpolar sub-phase formed by the alkyl side chains that may be present in some of the ions" 85 as found in molecular simulations of [RMIM] + salts due to Canongia Lopes et al, 83,86 and from small-wide angle X-ray scattering work, 87 demonstrated.…”
Section: Nernst-einstein Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…2 for a listing) and data for simple high-temperature molten salts. 1, 84 One may speculate that this change in ∆ is due to the "existence of a polar network formed by the charged moieties of the molecular ions" and "separations between different strands of the polar network caused by a continuous nonpolar sub-phase formed by the alkyl side chains that may be present in some of the ions" 85 as found in molecular simulations of [RMIM] + salts due to Canongia Lopes et al, 83,86 and from small-wide angle X-ray scattering work, 87 demonstrated.…”
Section: Nernst-einstein Equationmentioning
confidence: 99%
“…The different order for these last two quantities for [Tf 2 N]salts on the one hand and [BF 4 ]and [PF 6 ]salts on the other, as for the VCC, has yet to be explained, though it could be due to greater cation-cation contact when the anions are small as suggested by the molecular dynamics simulations of Klähn and Seduraman. 83 Linear and angular momentum exchange through translationalrotational coupling and caging of the smaller ions are other effects to be considered.…”
Section: Velocity Cross-correlation Coefficients and Distinct Diffusimentioning
confidence: 99%
“…Table S1 in supporting information). These are typical values for CT in ionic pairs as calculated accurately using a QM/MM approach for a variety of ILs in the liquid phase 32 .…”
Section: B Simulation Details -Methodologymentioning
confidence: 83%
“…This interpretation is supported by a recent study that molecular dynamics simulations of ten different pure and CO 2 saturated ionic liquids have shown a strong correlation between the ratio of unoccupied space in pure ILs and their ability to absorb CO 2 . 50 …”
Section: Resultsmentioning
confidence: 99%
“…16 Both of the cation and anion of [Bmpy][NTf 2 ] are large with weak electrostatic cation–anion interaction densities which allow a large number of unoccupied space in the IL for methanol adsorption but not for larger molecules. 50 …”
Section: Resultsmentioning
confidence: 99%